Hukum Cyber dan Implikasinya Terhadap Transaksi Ekonomi Syariah Berbasis Online - Rizal Renaldi; Bay Saputra (STAI Al Musaddadiyah Garut, 2026)
This study aims to analyze the implications of cyber law on online Islamic economic transactions and its contribution to the development of legal and Sharia economic studies in the digital era. Using a qualitative approach with a library research method, this study examines books, journal articles, regulations, fatwas, and other relevant academic publications concerning cyber law and Islamic commercial jurisprudence. The data were analyzed using content analysis techniques, including the identification of core concepts, categorization of legal issues, and synthesis of literature. The results indicate that the implementation of cyber law plays a significant role in securing Sharia-compliant digital transactions by strengthening authentication mechanisms, data protection, contract transparency, and the prevention of cybercrime. These findings generate an integrative conceptual framework that connects national cyber regulations with Sharia principles, forming a theoretical basis for understanding digital muamalah practices. The study concludes that harmonizing cyber law with Islamic legal values is essential to ensuring legal certainty, ethical conduct, and fairness in online Sharia transactions. Further research is recommended, particularly empirical studies, to evaluate platform compliance with Sharia requirements and assess the effectiveness of regulatory supervision in practical settings.